2014
DOI: 10.1016/j.jnucmat.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the tetragonal to monoclinic phase transformation during oxidation of zirconium alloys

Abstract: a b s t r a c tCorrosion is a key limiting factor in the degradation of zirconium alloys in light water reactors. Developing a mechanistic understanding of the corrosion process offers a route towards improving safety and efficiency as demand increases for higher burn-up of fuel. Oxides formed on zirconium alloys are composed of both monoclinic and meta-stable tetragonal phases, and are subject to a number of potential mechanical degradation mechanisms. The work presented investigates the link between the tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 43 publications
2
32
0
2
Order By: Relevance
“…The phase transformation has been represented as a volumetric or dilatational expansion via the expansion of a central set of truss elements (Fig.1). Each truss element within this central region increases in length by 0.019 (1.9%) in line with the hydrostatic strain defined in Eq.2 and the calculated strain tensors in (Platt et al, 2014).…”
Section: Phase Transformation Volumetric Expansionsupporting
confidence: 67%
See 4 more Smart Citations
“…The phase transformation has been represented as a volumetric or dilatational expansion via the expansion of a central set of truss elements (Fig.1). Each truss element within this central region increases in length by 0.019 (1.9%) in line with the hydrostatic strain defined in Eq.2 and the calculated strain tensors in (Platt et al, 2014).…”
Section: Phase Transformation Volumetric Expansionsupporting
confidence: 67%
“…The impact of variant selection and anisotropic material properties are not the main focus of this work, therefore for simplicity, the phase transformation has been simulated as a dilatational volumetric expansion. This is implemented via the hydrostatic strain, calculated from the strain tensors defined in (Platt et al, 2014), and shown in equation 2. The phase transformation has been represented as a volumetric or dilatational expansion via the expansion of a central set of truss elements (Fig.1).…”
Section: Phase Transformation Volumetric Expansionmentioning
confidence: 99%
See 3 more Smart Citations